2020
DOI: 10.21873/anticanres.14060
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sarcopenia and Clinical Outcomes in Patients With Esophageal Cancer Under Neoadjuvant Therapy

Abstract: Background/Aim: This study aimed to evaluate the association of sarcopenia and Clinical Outcomes with esophageal cancer under neoadjuvant chemoradiotherapy (CRT). Patients and Methods: A retrospective study assessing patients with esophageal cancer who underwent CRT between 2001 and 2014 was conducted in the medical center. Hospital patients' records on sarcopenia and treatment outcomes were statistically analyzed. Results: The sarcopenia group had significantly lower body mass index than the non-sarcopenia gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…In addition, the diagnosis of PS was an independent risk factor for mortality. The data revealed that the risk of sarcopenia and low muscle strength are associated with a worse postoperative outcome, corroborating the results of other authors [26][27][28][29] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the diagnosis of PS was an independent risk factor for mortality. The data revealed that the risk of sarcopenia and low muscle strength are associated with a worse postoperative outcome, corroborating the results of other authors [26][27][28][29] .…”
Section: Discussionsupporting
confidence: 90%
“…For instance, gastric cancer, whose treatment is predominantly surgical, is the fifth most common cancer and the third leading cause of death by cancer worldwide 1. Huang et al (2020) 29 showed that the overall and diseasefree survival were lower among the sarcopenic patients receiving neoadjuvant treatment for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of sarcopenia diagnosis varied among the included studies: before NAT (5), after NAT (5), or two time periods measured (1). Six studies reported prevalence of sarcopenia before or/and after neoadjuvant therapy, all eleven studies reported OS, but only three studies reported DFS (11,20,25). The follow-up time was relatively short with a median time ranging from 11 to 39 months, and some studies did not provide a follow-up time (14,23,25).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of sarcopenia in our cohort (64%) is consistent with the previously published prevalence [ 6 ]. Many studies have demonstrated that sarcopenia is associated with increased chemotherapy dose-limiting toxicity [ 9 ], CRT toxicity [ 7 , 8 , 9 , 36 ], and radiation treatment breaks [ 7 , 9 ]. However, an association between CRT-related hematologic toxicity and sarcopenia has not been demonstrated in OSCC.…”
Section: Discussionmentioning
confidence: 99%